Azospirillum brasilense Inoculation in a Maize–Urochloa–Rice Cropping System Promotes Soil Chemical and Biological Changes and Increases Productivity - Silva, Philippe Solano Toledo [UNESP]; Garcia, Nayara Siviero [UNESP]; Galindo, Fernando Shintate [UNESP]; Arf, Orivaldo [UNESP]; Nogueira, Thiago Assis Rodrigues [UNESP]; Jani, Arun Dilipkumar; Cassiolato, Ana Maria Rodrigues [UNESP] (MDPI, 2024)
Large quantities of cover crop residues in the soil, combined, or not, with the inoculation of seeds with diazotrophic bacteria, can increase organic matter (OM) and protect soil microorganisms, such as arbuscular mycorrhizal fungi (AMF) and dark septate endophytic (DSE) fungi. Thus, the use of these sustainable biotechnologies can benefit microbial interactions, soil fertility and rice production in the Brazilian Cerrado region. In this study, we evaluated the effects of maize and Urochloa ruziziensis, intercropped or individually, as cover crops and an inoculation of Azospirillum brasilense on the chemical (fertility) and biological (C–microbial biomass and C–CO2 released) attributes of soil and the effects of root colonization by AMF and DSE on the yield of rice grown in succession in highlands. The experiment was conducted under field conditions, in a typical dystrophic Red Oxisol. The experimental design consisted of randomized blocks arranged in strips, incorporating a combination of eight residual cover crops: ((1) maize, (2) maize–I (I = inoculation of seeds with A. brasilense), (3) Urochloa (U. ruziziensis), (4) Urochloa–I, (5) maize + Urochloa–I, (6) maize + Urochloa–I, (7) maize–I + Urochloa and (8) maize–I + Urochloa–I). This was accompanied by two treatments of rice as a successor crop (inoculated or not with A. brasilense), with four replicates, totaling 64 experimental units. A cover crop and rice seed inoculation prompted increases in OM and AMF relative to DSE, while the inoculation of rice, regardless of the cover crop treatment, increased the soil’s P content. The combination of maize + Urochloa–I and inoculated rice as the next crop generated increases in its sum of bases (SBs) and cation exchange capacity (CEC). There was a 19% increase in rice grain yields when the seed was inoculated.
Keywords: arbuscular mycorrhiza; dark septate endophytes; microbial activity; Oryza sativaL; sustainable agriculture